Assessing the Effectiveness of Social Media Promotion for ’Seruit Bu Lin’ in Bandar Lampung: An EPIC Model Approach - Putri, Gita Leviana; Mahmudah, Fitri Annisa Nuur; Angkupi, Prima; Barusman, Andala Rama Putra; Suharyo, Akhmad (Proceeding ICEBFG, 2024)
In 2023, Indonesia’s economic growth rate was 5.05%, driven significantly by the food and beverage industry, which plays a crucial role in the Creative Economy. This study evaluates the effectiveness of social media promotion for the culinary product "Seruit Bu Lin" using the EPIC model, focusing on Empathy, Persuasion, Impact, and Communication. Conducted in Bandar Lampung, the research targets followers of "Seruit Bu Lin" on Instagram and TikTok. Data were collected via a structured questionnaire and analyzed using SPSS version 27. The findings highlight the importance of demographic diversity, particularly the engagement of Generation Z and Millennials, and provide valuable insights into the strengths and weaknesses of promotional content. The study concludes that the EPIC model is a robust framework for assessing social media promotional effectiveness, offering actionable insights for developing targeted strategies to enhance engagement and effectiveness in the culinary sector.